Pengaruh Konsentrasi Bubur Bunga Kenop ( Gomphrena globosa L. ) Terhadap Karakteristik Selai - Keswari, Ni Kadek Ayumi Puri; Yusasrini, Ni Luh Ari; Permana, I Dewa Gde Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i01.p09, 2025)
The Globe Amaranth flowers contains antioxidant compounds, vitamin C, and betacyanin. This flower offers significant health benefits and has the potential to be developed into value-added food products, one of which is jam. Globe amaranth contains betacyanin, which gives it a red-purple pigment. The concentration of globe amaranth porridge used will naturally affect the resulting color of the jam. Additionally, the concentration of the main porridge ingredient influences the texture of the jam. The aim of this study is to evaluate the effect of various concentrations of globe amaranth porridge on jam characteristics and to determine the optimal concentration that yields the best quality jam. A Completely Randomized Design (CRD) was used, with five levels of globe amaranth porridge concentrations : 4.25%, 8.75%, 13.25%, 17.75%, and 22.25%. Each treatment level was repeated three times, resulting in a total of 15 experimental units. The data were analyzed using analysis of variance, followed by Duncan’s Multiple Range Test (DMRT) for significant results. The findings indicate that the concentration of globe amaranth porridge has significant effect and led to increases in total soluble solids, antioxidant activity, total betacyanin, and viscosity, as well as decreases in syneresis and spreadability, along with effects on the jam’s color, aroma, texture, taste, thickness, and overall acceptance. The best characteristics for globe amaranth jam were achieved with a porridge concentration of 17.75%, yielding a total soluble solid content of 65.70% Brix, antioxidant activity of 69.35%, total betacyanin of 0.31 mg/g, viscosity of 21.07 Pa.s, syneresis of 2.81%, spreadability moderately easy to spread, purple jam color with moderate preference, aroma and taste rated as moderately preferred, thick texture with neutral preference, and overall acceptance rated as neutral. Keywords : jam, globe amaranth flower, concentration